Mengintegrasikan Model Sekolah dan Pesantren untuk Meningkatkan Mutu Madrasah Indonesia di Era Globalisasi - Abdul Rohman; Siti Muhtamiroh (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
Pesantren, madrasas, and schools have changed dynamically in the last few decades in Indonesia. Dialogue, interaction, and interconnection occur dynamically between these three educational institutions in Indonesia. This study aims to explore the development of madrasas in response to changing world in the era of globalization. The study is qualitative in which data were collected through documentation studies, interviews, and observations. With descriptive-interpretive analysis, the study found that madrasas which are often claimed as underdeveloped institutions have been shown to be advanced educational institutions. Madrasas already have equality, even surpassing school educational institutions in Indonesia. The change and progress of these madrasas are achieved through implementing the pattern of pesantren as the basis of a learning system where all students are housed in a learning society, implementing a curriculum model that combines schools and pesantren, and applying a humanistic learning model in the educational process. Through these three aspects, madrasas can produce qualified graduates.